P-101 Incidence of Anti-drug Antibodies in Crohn's Disease Patients During 5 Years of Certolizumab Pegol Therapy. (March 2016) - Sandborn, William; Dubinsky, Marla; Kosutic, Gordana; Parker, Gerry; Spearman, Marshall; Hasan, Iram; Coarse, Jason; Ptak, Theodore; Younes, Ziad; Shafran, Ira; Lee, Scott; Afzali, Anita; et al.
Abstract : Background: Any biologic drug, whether human, chimeric, or "humanized, " can cause an immune response, leading to antidrug antibody (ADAb) formation which can cause treatment failure of tumor necrosis factor (TNF) antagonists. The prevalence of ADAb is dependent upon multiple factors, including assay type, route of administration, dosing schedule, and use of concomitant treatments. Currently, no robust long-term ADAb prevalence data exist for any of the TNF antagonists that are used to treat Crohn's disease. We evaluated the prevalence of certolizumab pegol ADAb (CZP-ADAb) with long-term treatment. Methods: Patients who enrolled in C87085 (a 6-week, randomized, placebo-controlled study) and either: (1) had disease deterioration in the first 2 weeks of the trial (defined as an increase in Crohn's disease activity index [CDAI] ≥70 points relative to baseline or absolute CDAI ≥350 points); or (2) completed the 6-week trial and were eligible for inclusion in C87088 (a 5-year, open-label extension [OLE] study). Regardless of treatment assignment during the placebo-controlled C87085 trial, all patients in C87088 received CZP induction of 400 mg at Weeks 0, 2, and 4, followed by maintenance therapy with CZP 400 mg every 4 weeks until week 262. Plasma concentrations of CZP and CZP-ADAb were measured by ELISA in samples collected prior to dosing at weeks 0, 6, 32, 52, 100, 160, 208, and the Final/Withdrawal visit. Patients were considered CZP-ADAb positive if the titer was >2.4 units/mL at any time. The cumulative frequency of patients with CZP-ADAb was defined as the number of patients who were CZP-ADAb positive at each visit (numerator) divided by the number of evaluable patients (denominator). Results: Overall, 10.2% (41/402) of patients were CZP-ADAb positive over the course of both studies; 3 patients (all in the C87085 CZP 400 mg group) had developed CZP-ADAb between the start of C87085 and the start of C87088. Development of CZP-ADAb most frequently occurred within the first 32 weeks of treatment during C87088. The cumulative frequency of CZP-ADAb detected was ⩽6.2% at each time point measured. As expected, geometric mean CZP plasma concentrations were substantially lower in patients who were CZP-ADAb positive (range of means during C87088: 0.88–15.25 μg/mL, excluding the Withdrawal visit) compared with those who were CZP-ADAb negative (range of means during C87088: 8.33–29.89 μg/mL, excluding the Withdrawal visit). No meaningful differences were observed in the types or prevalence of adverse events (AEs), serious AEs, or AEs leading to discontinuation of medication\study withdrawal between ADAb-positive and -negative patients based on CZP-ADAb status. Conclusions: A total of 41 patients (10.2%) were CZP-ADAb positive over the course of both the qualifying study (C87085) and this 5-year OLE study, C87088. Meaningful differences in AEs, serious AEs, or AEs leading to withdrawal based on CZP-ADAb status were not observed. Given the small number of patients who were positive for CZP-ADAb, no conclusions can be drawn with regard to the effect of CZP-ADAb status on disease improvement with treatment. clinicaltrials.gov identifier: NCT00552058, NCT00552344 UCB Pharma-sponsored study